Effect of aqua raw and non-protein extracts of Melia azedarach and Lactuca serriola on some biochemical variables in healthy rats and with dioxan-induced diabetes rats - Nahida Al-Chalaby; Khalid Almanaa (College of Education for Pure Sciences, 1970)
Abstract The activity of hypoglycemic, hypocholesterolemic, hypolipidemic of crude, non-proteinous cold aqueous extracts of Melia azedarach and Lactuca serriola plants and boiled non-proteinous extract of Melia azedarach have been studied after intraperitoneal injection in normal and alloxan- induced diabetic rats. After two hours of intraperitoneal injection of cold crude aqueous extract of the leaves of Lactuca serriola at a dose (50 mg/kg of body weight). The results indicated a significant decrease in glucose and total lipids levels and insignificant decrease in cholesterol level, hence, the effects of the cold crude aqueous extract are similar to those of the insulin in alloxan diabetic rats. In main time, the same extract has led to a significant decrease just in glucose level in non-diabetic rats. The cold crude aqueous extract of Melia azedarach, produced no significant changes in normal and alloxan diabetic rats, but a significant decrease in total lipids level for diabetic rats, whereas the non-proteinous extract of the same plant showed a significant decrease in glucose, cholesterol and total lipids levels in alloxan diabetic rats but not in normal rats. In conclusion, results indicated that cold crude aqueous extract of the leave of Lactuca serriola plant posses hypoglycemic and a decrease in total lipid effect, but non-proteinous cold extract for the leave of Melia azedarach posses hypoglycemic, decrease for the levels of cholesterol and total lipids in blood serum of diabetic rats and this extracts may be used for treating diabetes mellitus after sure that there is no side effects